(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
This article highlights the role and importance of local infiltration anesthesia in surgical practice. Information is provided about the essence of infiltration anesthesia, its mechanism of action, methods of application, and the main anesthetic drugs used in surgical practice. In addition, the advantages, disadvantages, and possible complications of this method are also analyzed. According to the research results, infiltration anesthesia is considered one of the effective and safe methods of pain relief in minor surgical operations.